The typical presentation of an atypical pathogen during an outbreak of Legionnaires' disease in Vila Franca de Xira, Portugal, 2014 - Dias, A (2018)
Copyright © 2017 Sociedade Portuguesa de Pneumologia. Published by Elsevier España, S.L.U. All rights reserved.